Searching for potential multi-hazard events during the last 1.5 million years of the Pleistocene epoch - Balazs Bradak; Christopher Gomez; Thomas Stevens; Ákos Kereszturi (Forum Geografi, 2022)
Increasing attention has been paid to multi-hazards in environmental disaster studies produced during the last decade. Multi-hazard studies focus on the occurrence, interaction and effect of several natural hazards in the same region. Despite the increasing number of multi-hazard studies, few investigations have focused on global-scale multi-hazard events. With the aim of closing this gap, our study focuses on the identification of periods during the last 1.5 million years of the Pleistocene epoch, with the quasi-parallel appearance of natural hazards (e.g., asteroid impacts and large volcanic eruptions with a Volcanic Explosivity Index (VEI) of 8 and 7) amplifying their individual effects and thus causing long-term, global-scale changes. Of the seven identified potential multi-hazard events, three were considered as possible global-scale events with a longer term environmental (paleoclimatic) impact; dated to c.a., 1.4 Ma (marine isotope stage – MIS45), 1.0 Ma (MIS 27), and 100 ka (MIS 5c), respectively. Two additional periods (around 50 and 20 ka) were identified as being associated with more restricted scale multi-hazard events, which might cause a “Little Ice Age-like” climatic episode in the history of the Pleistocene Period. In addition, we present a hypothesis about the complex climatic response to a global-scale multi-hazard event consisting of a series of asteroid impacts and volcanic eruption linked to a geomagnetic polarity change, namely the Matuyama-Brunhes Boundary, which might be accompanied by global cooling and result in the final step of the Early Middle Pleistocene Transition.